A Unified Integrated Public Health Approach: Zika Response - Betsy Kagey; Jennifer Burkholder (Georgia Southern University, 2017)
Background: Zika virus planning in Georgia has involved many units within the Georgia Department of Public Health (GDPH). Their roles and responsibilities include identifying potential vectors, alerting and educating the public on how to 'tip n toss', preparing and testing for Zika virus infection at the Georgia Public Health Laboratory (GPHL), monitoring travelers, including pregnant women, infected with Zika virus, direct messaging for pregnant women, mothers of newborns and women who are considering pregnancy, and education on sexual transmission for men and women. Methods: With no locally transmitted case of Zika virus infection within Georgia, the focus has been on public messaging and answering the myriad calls about Zika virus from health care providers and the public. This unified response involves numerous GDPH units: Epidemiology, Maternal and Child Health, GPHL, Emergency Preparedness and Response (EPR), Environmental Health, Risk Communication, WIC, and others. Conclusions: The Office of Public Health Emergency Preparedness and Response is one member of this multi-unit team. This session will identify the roles and responsibilities of each of these units in the unified response to Zika virus within Georgia both at the state and district level. Lessons learned from this approach build upon GDPH's overall capacity to provide an integrated respond to public health threats and emergencies within the state. Key words: integration, public health, emergency preparedness, Zika response